1994
DOI: 10.1177/089826439400600303
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Health Locus of Control and the Use of Medical Care Services

Abstract: Health locus of control, the extent to which one believes he or she can affect his or her health status, usually is viewed as one of the factors that predisposes individuals to use medical services. However, some social theorists outside the area of utilization studies suggest that locus of control beliefs also are consequences of health-related behaviors and events such as utilization. The authors address this issue by investigating the relationship between health locus of control and utilization of medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Patients who scored higher on the Powerful Others and/or Chance dimensions were likely to have higher utilization rates, while those who scored higher on the Internal construct were likely to have fewer visits to the ED, fewer hospital admissions, and fewer ambulatory physician visits (Bazargan et al, 1998; Chambers et al, 2013). Similarly, Goldsteen et al (1994) also reported that patients with more of a Powerful Others locus of control (PLOC) and/or Chance locus of control (CLOC) were likely to have a higher incidence of hospitalizations and physician visits. Additionally, patients’ PLOC has been shown to positively correlate with trust in physicians (Brincks et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Patients who scored higher on the Powerful Others and/or Chance dimensions were likely to have higher utilization rates, while those who scored higher on the Internal construct were likely to have fewer visits to the ED, fewer hospital admissions, and fewer ambulatory physician visits (Bazargan et al, 1998; Chambers et al, 2013). Similarly, Goldsteen et al (1994) also reported that patients with more of a Powerful Others locus of control (PLOC) and/or Chance locus of control (CLOC) were likely to have a higher incidence of hospitalizations and physician visits. Additionally, patients’ PLOC has been shown to positively correlate with trust in physicians (Brincks et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…For example, those who have a high Chance health LOC orientation are likely to be less engaged in positive health behaviors, whereas those high on the Internal dimension are more likely to have a health-oriented approach (Ludenia and Donham, 1983; Norman and Bennett, 1996). Researchers have demonstrated a relationship between health LOC and patients’ healthcare utilization in specific contexts (Bazargan et al, 1998; Chambers et al, 2013; Goldsteen et al, 1994). Patients who scored higher on the Powerful Others and/or Chance dimensions were likely to have higher utilization rates, while those who scored higher on the Internal construct were likely to have fewer visits to the ED, fewer hospital admissions, and fewer ambulatory physician visits (Bazargan et al, 1998; Chambers et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Health locus of control is viewed as one of the factors that predisposes individuals to use medical services [5]. On the other hand, health locus of control beliefs are also consequences of health-related behaviours and events such as utilisation [5]. An external orientation may also be advantageous in situations in which little personal control is possible [13].…”
Section: Introductionmentioning
confidence: 99%
“…External locus of control measures correlated negatively with dispositional optimism [8]. Health locus of control is viewed as one of the factors that predisposes individuals to use medical services [5]. On the other hand, health locus of control beliefs are also consequences of health-related behaviours and events such as utilisation [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation